Pengaruh Pendidikan Kesehatan dengan Whatsapp Tentang Imunisasi DPT (Difteri, Pertusis dan Tetanus) dan Kipi (Kejadian Ikutan Pasca Imunisasi) Terhadap Pengetahuan dan Sikap Ibu - Neneng Gia Defilza; Meri Neherta; Deswita Deswita (Universitas Batanghari Jambi, 2021)
Immunization coverage may decrease by more than 35% in May 2020 compared to the same time period in the previous year. Mother's knowledge about DPT immunization and KIPI plays an important role in determining the success of immunization implementation. During the Covid-19 pandemic, all public activities were restricted. However, health promotion in infants must still be implemented to increase the knowledge and awareness of parents bringing their children to do it. This study aims to see the effect of health education using WhatsApp on the knowledge and attitudes of mothers about DPT immunizations and KIPI. The study used a quasi-experimental pretest – posttest control design. The sample consisted of 64 respondents consisting of 32 people in the intervention group and 32 people in the control group. Sampling by simple random sampling. The instrument used was questionnaire provided in the form of google form. The results showed that there was a significant effect of health education on knowledge (p value = 0.000) and attitudes (p value = 0.000) of respondents in the intervention group. However, there was no effect on the control group, knowledge (p value = 0.184) and attitude (p value = 0.325) of respondents. Suggestions for the health promotion team to continue to provide health promotion during the pandemic by using whatsapp media. So that the promotion can still be carried out without having to collect respondents.